2015
DOI: 10.1159/000437035
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Ultrasonography in Inflammatory Bowel Disease

Abstract: Background: The diagnosis of inflammatory bowel disease (IBD) is based on a combination of endoscopic, clinical and biochemical investigations as well as cross-sectional imaging. The applications of cross-sectional imaging in IBD are manifold. Ultrasonography has emerged as an important imaging modality in the diagnosis of Crohn's disease (CD) as well as for monitoring disease progression and in the therapeutic response to CD and ulcerative colitis (UC). Key Messages: Ultrasonography is non-invasive, radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…Our study agreed with different trials in which it was shown that diagnosis of IBD and assessment of its activity cannot be dependent on clinical evaluation alone but should by combined with other investigations such as biomarkers, endoscopy, and imaging techniques such as bowel ultrasound and MRE[ 25 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study agreed with different trials in which it was shown that diagnosis of IBD and assessment of its activity cannot be dependent on clinical evaluation alone but should by combined with other investigations such as biomarkers, endoscopy, and imaging techniques such as bowel ultrasound and MRE[ 25 , 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that there is no clear gold standard imaging technique for IBD diagnosis including MRE or bowel ultrasound which could be used besides clinical history, biomarkers, endoscopy for diagnosis of IBD as agreed with previous studies[ 25 , 30 , 36 ].…”
Section: Discussionsupporting
confidence: 80%
“…The diagnosis of IBD is confirmed by clinical evaluation and by a combination of other investigative modalities, including history, biomarkers, endoscopy, and cross-sectional imaging such as IUS. As a current methodology with a high negative predictive value, IUS is accepted as a first-line tool in the primary diagnosis workup of adults and children with suspected small bowel inflammation [ 30 , 43 - 46 ]. If the appropriate expertise is available, IUS could also be used as a primary diagnostic modality in adult CD patients and MRI could be reserved for patients with unclear findings or symptoms.…”
Section: When To Use Ius In Ibd Patientsmentioning
confidence: 99%
“…Although Doppler sonography does not constitute a routine first-line tool for the initial diagnosis of CD, it has been proposed as a potential adjunct method for the follow-up of patients [45]. Nevertheless, in this study, results from imaging methods, MRE and USCD, showed no significant agreement with the clinical CD activity, and with the currently used biomarkers, serum CRP and fecal calprotectin.…”
Section: Discussionmentioning
confidence: 59%